2011
DOI: 10.1007/s11250-011-9850-0
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of colour in fat-tailed sheep: a review

Abstract: Fat-tailed sheep come in various colours-most are either brown (tan) or black. In some, most of the body is white with the tan or black colour restricted to the front portion of the body or to just around the eyes, muzzle and parts of the legs. The Karakul breed is important for the production of lamb skins of various colours for the fashion industry. As well as the black and tan colours there are Karakuls bred for grey or roan shades, a white colour or one of the numerous Sur shades. In the Sur shades, the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
(16 reference statements)
1
17
0
2
Order By: Relevance
“…Allele E D , which was subsequently characterized at the molecular level (Våge et al, 1999), is directly involved in sheep pigmentation (Lundie, 2004). Our data indicated that this allele is also clearly responsible for the wool color variation in Creole sheep, particularly determining the black phenotypes.…”
Section: Discussionmentioning
confidence: 62%
“…Allele E D , which was subsequently characterized at the molecular level (Våge et al, 1999), is directly involved in sheep pigmentation (Lundie, 2004). Our data indicated that this allele is also clearly responsible for the wool color variation in Creole sheep, particularly determining the black phenotypes.…”
Section: Discussionmentioning
confidence: 62%
“…Existem dois tipos principais de melaninas, a eumelanina (pigmento preto ou marrom) responsável por animais de fenótipo entre marrom e preto, e a feomelanina (pigmento vermelho ou amarelo) a qual resulta em lãs com tons avermelhados, bronzeados ou fulvos (Lundie, 2011). A essência das variações de coloração da pelagem da ovelha doméstica (Ovis aries) e os padrões destas, decorrem das quantidades e proporções de melaninas produzidos nas células dos folículos de lã e transportados para a pele e os fios de lã e/ou cabelo (Cockett;Shay & Smit, 2001;Deng et al, 2009).…”
Section: A Pigmentação Da Lãunclassified
“…The study of color is an important part of the morphological characterization of domestic animals, which is in turn a very important aspect of livestock breed conservation (Alderson, 2018). Sheep color varies widely, although breeders targeting wools for industry have focused on white wool and have penalized colored fleeces (Adalsteinsson 1970, Sponenberg, 1997, Lundie 2011. Selection for whiteness has decreased the frequency of alleles that produce color, although these persist in many breeds as recessive variants.…”
Section: Introductionmentioning
confidence: 99%
“…Production of colored wool persists and provides value to those breeders involved. Previous studies have documented various alleles at the highly variable Agouti Signaling Protein locus, Melanocortin 1 receptor locus, and Tyrosinase Related Protein 1 locus (Adalsteinsson, 1970;Lundie, 2004, Lundie 2011, Sponenberg 1997.…”
Section: Introductionmentioning
confidence: 99%